The rough colony morphotype of Mycobacterium avium exhibits high virulence in human macrophages and mice. Issue 7 (26th July 2020) - Nishimura, Tomoyasu; Shimoda, Masayuki; Tamizu, Eiko; Uno, Shunsuke; Uwamino, Yoshifumi; Kashimura, Shoko; Yano, Ikuya; Hasegawa, Naoki
Abstract : Introduction. The incidence of Mycobacterium avium complex (MAC) pulmonary disease (MAC PD), a refractory chronic respiratory tract infection, is increasing worldwide. MAC has three predominant colony morphotypes: smooth opaque (SmO), smooth transparent (SmT) and rough (Rg). Aim. To determine whether colony morphotypes can predict the prognosis of MAC PD, we evaluated the virulence of SmO, SmT and Rg in mice and in human macrophages. Methodology. We compared the characteristics of mice and human macrophages infected with the SmO, SmT, or Rg morphotypes of M. avium subsp. hominissuis 104. C57BL/6 mice and human macrophages derived from peripheral mononuclear cells were used in these experiments. Results. In comparison to SmO- or SmT-infected mice, Rg-infected mice revealed severe pathologically confirmed pneumonia, increased lung weight and increased lung bacterial burden. Rg-infected macrophages revealed significant cytotoxicity, increased bacterial burden, secretion of proinflammatory cytokines (TNF-α and IL-6) and chemokines (CCL5 and CCL3), and formation of cell clusters. Rg formed larger bacterial aggregates than SmO and SmT. Cytotoxicity, bacterial burden and secretion of IL-6, CCL5 and CCL3 were induced strongly by Rg infection, and were decreased by disaggregation of the bacteria. Conclusion. M. avium Rg, which is associated with bacterial aggregation, has the highest virulence among the predominant colony morphotypes.